Electrical characteristics and influence of the air-gap size in a trielectrode plasma curtain at atmospheric pressure - Sosa, Roberto (2009)
A study of the electrical characteristics of the trielectrode plasma curtain (TPC) discharge is presented. The influence of the air-gap size (for a fixed value of the inter-electrode distance) on the discharge behaviour has been exhaustively studied. The TPC discharge is based on the combination of a dielectric barrier discharge (DBD) with a corona discharge (CD) in a three electrode system, and basically it consists of the 'stretching' of a pure DBD by the action of a negative CD generated between the active electrode of the dielectric barrier and a remote third electrode. It was found that the general trend of the electrical characteristic curves (the average discharge current and the streamer frequency as functions of the AC and DC biasing voltages) was very similar for all the air-gap values considered. Our results indicate that the development of the TPC discharge requires two conditions: (a) the presence of a positive cycle of a well-developed DBD together with a CD where the remote electrode acts as the cathode and (b) a voltage drop between the DBD electrode and the remote electrode high enough to obtain an average electric field in the gap that must exceed a minimum average electric field value in the streamer channel necessary for its propagation across the gap (≈6.3 kV cm-1 in our experimental conditions). © 2009 IOP Publishing Ltd.